2022
DOI: 10.18502/kss.v7i8.10732
|View full text |Cite
|
Sign up to set email alerts
|

Students' Anxiety in Speaking in Front of the Class

Abstract: This study investigated the factors that cause students to feel anxious during impromptu activities in speaking class. Qualitative descriptive methods were employed. An openended questionnaire was used to collect the data. Nine students from class A in the second semester of the academic year 2019/2020 took part in this study. They were majoring in English education at one of Southeast Sulawesi’s higher education institutes, and they had speaking anxiety when performing impromptu activities in speaking class. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Von Wörde (2003) and Humaera & Pramustiara (2022) in their study tends to support those of other studies in that they show that anxiety can have a variety of detrimental effects on language learning and that reducing anxiety appears to improve language acquisition, retention, and learner motivation. As a result, it is advised that both teachers and students raise their awareness of and take careful note of foreign language anxiety.…”
Section: Literature Reviewmentioning
confidence: 55%
See 2 more Smart Citations
“…Von Wörde (2003) and Humaera & Pramustiara (2022) in their study tends to support those of other studies in that they show that anxiety can have a variety of detrimental effects on language learning and that reducing anxiety appears to improve language acquisition, retention, and learner motivation. As a result, it is advised that both teachers and students raise their awareness of and take careful note of foreign language anxiety.…”
Section: Literature Reviewmentioning
confidence: 55%
“…This affects students' willingness to participate in the learning process (Humaera, Jumiati & Safei, 2022;Humaera & Pramustiara, 2022). anxious student may have difficulty paying attention to what needs to be learned, processing information effectively, retrieving information, and demonstrating previously learned skills.…”
Section: Factors Contribute To Anxiety Comes From Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the results of the interviews, most students stated that they would feel nervous when they were suddenly asked to speak in front of the class, without any preparation. Humaera and Pramustiara (2022) stated that during impromptu activities students tend to have feelings of nervousness, fear and worry, and lack of vocabulary.…”
Section: Factors Causing Student' Anxiety In Speaking Englishmentioning
confidence: 99%
“…The study conducted by Asysyfa (2019), shows several factors that cause students' anxiety in speaking English, they are lack of preparation, afraid of not understanding the material said by the teacher, afraid of being wrong, fear of being considered bad and then being ridiculed by friends, lack of confidence in spelling, pronouncing, and choosing English words. Study conducted by Humaera and Pramustiara (2022), showed that students feel nervous, afraid, and worried, when asked to speak impromptu in the learning process.…”
Section: Introductionmentioning
confidence: 99%